2020
DOI: 10.3390/cryst10060545
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Mechanical Characteristics for Fiber-Reinforced Concrete with Straight and Hooked Fibers

Abstract: Fiber-reinforced concrete has a wide application in practice, and many fields of research are devoted to it. In most cases, this is a specific problem, i.e., the determination of the mechanical properties or the test method. However, wider knowledge of the effect of fiber in concrete is unavailable or insufficient for selected test series that cannot be compared. This article deals with the processing of a comprehensive test study and the impact of two types of fibers on the quantitative and qualitative parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 26 publications
1
31
1
Order By: Relevance
“…Research on the addition of steel fibers in OPC concrete to enhance the performance has been extensively studied by many researchers [ 24 , 25 , 26 ] over the world but is quite limited to fly ash-based geopolymer concrete. In the production of geopolymer concrete, the chemical composition of raw material, which is fly ash, is not standardized, especially as it comes from different sources.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the addition of steel fibers in OPC concrete to enhance the performance has been extensively studied by many researchers [ 24 , 25 , 26 ] over the world but is quite limited to fly ash-based geopolymer concrete. In the production of geopolymer concrete, the chemical composition of raw material, which is fly ash, is not standardized, especially as it comes from different sources.…”
Section: Introductionmentioning
confidence: 99%
“…This means that even after the initial tensile crack is formulated, the capacity to carry a higher tensile load still remains because of the substantial bridging effect of the fibers between cracks in the cement matrix. Adding fibers leads to enhanced mechanical properties such as matrix strength and fracture energy, especially in the tensile region [5]. Therefore, various HPFRCC production methods, such as engineered cementitious composite (ECC), slurry infiltrated fiber concrete (SIFCON), and reactive powder concrete (RPC), have been developed [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies point out that the bonding between the fibre and the matrix can be effectively improved by changing the shape of the fibre, thus improving the efficiency of the fibre. Marcalikova et al [ 5 ] compared the effect of different amounts of hooked and straight fibres on the mechanical properties of concrete and the results showed that the increase in fracture energy was more pronounced in the case of hooked fibre and that the hooked fibre also had a more significant positive effect on the tensile and shear strength of the concrete.…”
Section: Introductionmentioning
confidence: 99%